2010
DOI: 10.1016/j.jns.2010.06.012
|View full text |Cite
|
Sign up to set email alerts
|

VEGF/VEGFR-2 changes in frontal cortex, choroid plexus, and CSF after chronic obstructive hydrocephalus

Abstract: Chronic Hydrocephalus (CH) is often associated with decreased cerebral blood flow (CBF) and oxygen levels. While the exact pathophysiology is not clear, vascular endothelial growth factor (VEGF) and its receptor-2 (VEGFR-2) may be involved. Because the choroid plexus (CP) is involved in cerebrospinal fluid (CSF) production and secretes numerous growth factors including VEGF, it is important to understand VEGF/VEGFR-2 levels in the CP-CSF circulatory system. Our results showed significant decreases in CBF and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
(74 reference statements)
0
20
0
Order By: Relevance
“…Some previous studies also reported that VEGF was increased in the CSF of patients with post-hemorrhagic hydrocephalus [6] or chronic obstructive hydrocephalus [23]. Heep et al [6] demonstrated that in neonates, the CSF VEGF levels of patients with post-hemorrhagic hydrocephalus were significantly elevated compared to those of patients with non-hemorrhagic hydrocephalus, even though the CSF VEGF levels of post-hemorrhagic and non-hemorrhagic hydrocephalus patients were increased compared to those of the non-hydrocephalic neonate controls.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies also reported that VEGF was increased in the CSF of patients with post-hemorrhagic hydrocephalus [6] or chronic obstructive hydrocephalus [23]. Heep et al [6] demonstrated that in neonates, the CSF VEGF levels of patients with post-hemorrhagic hydrocephalus were significantly elevated compared to those of patients with non-hemorrhagic hydrocephalus, even though the CSF VEGF levels of post-hemorrhagic and non-hemorrhagic hydrocephalus patients were increased compared to those of the non-hydrocephalic neonate controls.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of VEGF are transduced mainly by two high-affinity receptors belonging to the tyrosine kinase-family: the fms-like tyrosine kinase (Flt-1) and the fetal liver kinase-1/kinase insert domain-containing receptor (Flk-1/KDR). The CP has been shown to contain mRNA (Nico et al 2004) and protein (Witmer et al 2002, Maharaj et al 2008, Yang et al 2010) of VEGF receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The choroid plexus shows high levels of VEGF (36), and its expression has been located on the epithelial cells (26,36,37,38). The effect of elevated VEGF levels in CSF has not been reported, although it is known that elevated VEGF levels in the brain increase the vascular permeability due to the effect of VEGF on endothelial cell junctions and fenestrations in endothelial cells.…”
Section: Resultsmentioning
confidence: 99%